z+97=180

Simple and best practice solution for z+97=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z+97=180 equation:


Simplifying
z + 97 = 180

Reorder the terms:
97 + z = 180

Solving
97 + z = 180

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-97' to each side of the equation.
97 + -97 + z = 180 + -97

Combine like terms: 97 + -97 = 0
0 + z = 180 + -97
z = 180 + -97

Combine like terms: 180 + -97 = 83
z = 83

Simplifying
z = 83

See similar equations:

| 6xyz+16xy= | | r^2+576=2r^2+32r+1024 | | 3ab+6ac-9ad= | | r^2+576=r^2+32r+1024 | | 15=-3x+4 | | 9+3(3u-7)=-3(3u-1)+8u | | 3x^2+x=-5 | | 5x+77=97 | | m^3n^2p^4+m^4n^3p^5-m^6n^4p^4+m^2n^4p^3= | | 5(u-5)-6=-3(-6u+9)-3u | | -3y+15x=24 | | 20x-12xy+4xz= | | (6-2x)*(-4)=8 | | Tan(65)=x/10 | | 6x-6+2(2x+6)=-4(x+3) | | 7x-4+66=180 | | 4[x-8]=3x+5 | | (x-4)=(x+7) | | z+66=180 | | 30-4(6)= | | 2(4-3x)-3(2x+1)=7(5x+2)-103 | | 254=139-y | | 4a^3bx-4bx= | | tan(-x)=5/8 | | 8(0+2y)=16(30-4y) | | 9/-4=-2 | | 8x-34+118=180 | | 6x-0=-16 | | 0.5x-0.4y=2.6 | | -0.75+0.4= | | m^2+23m+24=1 | | 2(r+-130)+2r=1660 |

Equations solver categories